Bunch quality and fertility of Vitis vinifera L. cv. Prime as affected by gibberellic acid (GA3) and s-abscisic acid (s-ABA). - Masikane, Nonkululeko Nosipho (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.